Analysis of mental toghness of women's rugby athletes at different levels - Nauroh, Qitarah; Komarudin, Komarudin; Saputra, Mochamad Yamin; Novian, Geraldi (Universitas Tanjungpura, 2025)
Background. Female rugby athletes at various levels of competition face different pressures, both physically and psychologically, which can affect the consistency and effectiveness of the game, so rugby athletes need to have good mental toughness. However, there are still limitations in research that compare the mental toughness of female rugby athletes at different levels of various factors that affect the effectiveness of mental training programs applied in the team. Objectives. This study aims to compare the mental toughness of female rugby athletes at various levels of competition. Methods. The subjects of the study involved 36 athletes competing in the sevens number at three different levels of competition (city, province, and national). The method used in this study is descriptive quantitative using the Sports Mental Training Questionnaire (SMTQ) as a research instrument. Results. The results showed differences in scores at three levels of competition, namely City, Province, and National. The city level has a percentage of athlete mental toughness of 77%, the provincial level has a percentage of athlete mental toughness of 82%, and the national level has a percentage of mental toughness of 85%. Based on the study that has been conducted, it can be concluded that there are differences in mental toughness in female rugby athletes at the city, provincial, and national levels. Conclusion. At the city level, the level of mental toughness is lower than at other levels, while at the national level, the mental toughness is higher than at others. This means that the higher the level of competition that rugby athletes participate in, the higher their mental toughness. Thus, this study can provide recommendations to practitioners in the sport of Rugby to manage the mental toughness of athletes at every level of competition.